Erythropoietin in traumatic brain injury (EPO-TBI): a double-blind randomised controlled trial. Issue 10012 (19th December 2015) - Nichol, Alistair; French, Craig; Little, Lorraine; Haddad, Samir; Presneill, Jeffrey; Arabi, Yaseen; Bailey, Michael; Cooper, D James; Duranteau, Jacques; Huet, Olivier; Mak, Anne; McArthur, Colin; et al.
Summary: Background: Erythropoietin might have neurocytoprotective effects. In this trial, we studied its effect on neurological recovery, mortality, and venous thrombotic events in patients with traumatic brain injury. Methods: Erythropoietin in Traumatic Brain Injury (EPO-TBI) was a double-blind, placebo-controlled trial undertaken in 29 centres (all university-affiliated teaching hospitals) in seven countries (Australia, New Zealand, France, Germany, Finland, Ireland, and Saudi Arabia). Within 24 h of brain injury, 606 patients were randomly assigned by a concealed web-based computer-generated randomisation schedule to erythropoietin (40 000 units subcutaneously) or placebo (0·9% sodium chloride subcutaneously) once per week for a maximum of three doses. Randomisation was stratified by severity of traumatic brain injury (moderate vs severe) and participating site. With the exception of designated site pharmacists, the site dosing nurses at all sites, and the pharmacists at the central pharmacy in France, all study personnel, patients, and patients' relatives were masked to treatment assignment. The primary outcome, assessed at 6 months by modified intention-to-treat analysis, was improvement in the patients' neurological status, summarised as a reduction in the proportion of patients with an Extended Glasgow Outcome Scale (GOS-E) of 1–4 (death, vegetative state, and severe disability). Two equally spaced preplanned interim analyses were done (after 202 and 404 participants were enrolled). This study is registered with ClinicalTrials.gov, number NCT00987454 . Findings: Between May 3, 2010, and Nov 1, 2014, 606 patients were enrolled and randomly assigned to erythropoietin (n=308) or placebo (n=298). Ten of these patients (six in the erythropoietin group and four in the placebo group) were lost to follow up at 6 months; therefore, data for the primary outcome analysis was available for 596 patients (302 in the erythropoietin group and 294 in the placebo group). Compared with placebo, erythropoietin did not reduce the proportion of patients with a GOS-E level of 1–4 (134 [44%] of 302 patients in the erythropoietin group vs 132 [45%] of 294 in the placebo group; relative risk [RR] 0·99 [95% CI 0·83–1·18], p=0·90). In terms of safety, erythropoietin did not significantly affect 6-month mortality versus placebo (32 [11%] of 305 patients had died at 6 months in the erythropoietin group vs 46 [16%] of 297 [16%] in the placebo group; RR 0·68 [95% CI 0·44–1·03], p=0·07) or increase the occurrence of deep venous thrombosis of the lower limbs (48 [16%] of 305 vs 54 [18%] of 298; RR 0·87 [95% CI 0·61–1·24], p=0·44). Interpretation: Following moderate or severe traumatic brain injury, erythropoietin did not reduce the number of patients with severe neurological dysfunction (GOS-E level 1–4) or increase the incidence of deep venous thrombosis of the lower limbs. The effect of erythropoietin on mortality remains uncertain. Funding: The National Health and Medical Research Council and the Transport Accident Commission.